Digital divide technology and our future - Pearson, Charlie; Studio Miramar; Films for the Humanities (Firm); Independent Television Service (Princeton, NJ : Films for the Humanities & Sciences, 2000)
Part one shows visits to several high schools in an examination of the push to wire America's schools and the effectiveness of incorporating the new computer technology into the curriculum. Part two looks at economic challenges to community and home access to computers and the Internet, and explores the fundamental alienation felt by many girls and students of color in the computer world, and the need for fostering an environment of inclusion
Subtitle from container
Executive producer, David Bolt
Narrated by Queen Latifah
DVD Format
Keywords: Computer-assisted instruction -- Social aspects -- United States; Educational technology -- United States; Internet in education -- United States; Computers and children; Educational equalization -- United States; Digital divide -- United States